Harley Quinn. The complete first season [videorecording (DVD)]. (Warner Bros. Home Entertainment : Warner Bros. Entertainment Canada Inc., 2020)
The series focuses on a single Harley Quinn, who sets off to make it on her own in Gotham City. Harley Quinn has finally broken things off once and for all with the Joker and attempts to make it on her own as the criminal Queenpin of Gotham City in this half-hour adult animated action-comedy series. With the help of Poison Ivy and a ragtag crew of DC castoffs, Harley tries to earn a seat at the biggest table in villainy: the Legion of Doom!